EFL Students’ Voices of Willingness to Communicate in Learning Interaction at the University Level - Artha, Anggraini Kesuma Dwindha; Susanto, Fajar (JET ADI BUANA, 2024)
One of the affective factors which influences the success of foreign language learning is Willingness to Communicate (WTC). WTC is a student’s tendency to involve or not to engage in a communication in a foreign language learning. This study aims to investigate the contributing factors influencing student’s willingness to communicate in English as a foreign language (EFL) at the university level. This research adopted a qualitative case study where interviews were conducted with four students of English Language Education Department at AB University in Surabaya and observations were also carried out to get additional information. Personal interviews were utilized to obtain primary data, while observation was used as complementary data focusing only on question-and-answer activities during the learning process. The findings of this study show that having English partner, self-confident, achievement in the study, interesting topic are the clear factors of the EFL student's willing to communicate in learning process. Therefore, it is advised that English teachers focus more on certain factors that affect students' WTC in order to assist the students in raising their WTC, which improves speaking.